Recent changes (2018-2022) in Benthic cover in Tubbataha Reefs Natural Park, Sulu Sea, the Philippines - Cadiz, Maria Michelle F.; Parr, Rhiana Angelita R.; Feliciano, Giannina Nicole R.; Alarcon, Rowell C.; Alaba, Maria Retchie P.; Pecson, Mary Joan M.; Licuanan, Wilfredo Y. (2024)
Tubbataha Reefs Natural Park is a benchmark for reef condition in the Philippines. However,
there has been a notable decline in hard coral cover from 2018–2022, coinciding with an increase in sponges and cyanobacteria – changes that were earlier posited to be due to eutrophication. Over the five-year time series used in this study, changes in the studied benthic components (hard coral, soft coral, sponges, macroalgae, turf algae, and cyanobacteria) did not all align with expected changes for a reef system experiencing nutrient enrichment. Moreover, these changes were not statistically significant at most spatial scales, and only turf algae and cyanobacteria exhibited significant changes with adequate statistical power at any given spatial scale. At present, nutrient enrichment cannot be confirmed nor completely ruled out as the main driver of the changes seen. Other drivers of change such as typhoon impacts must also be considered.
The shortage of statistically powerful results indicates the need for a more robust dataset before a conclusive cause for the changes in the cover of benthic components can be drawn.
Keywords: Natural history -- Philippines -- Tubbataha Reefs; Coral reef conservation -- Philippines -- Tubbataha Reefs